Preliminary study of a separative shared control scheme focusing on control-authority and attention allocation for multi-limb disaster response robots. (2nd May 2020) - Kamezaki, Mitsuhiro; Katano, Takahiro; Chen, Kui; Ishida, Tatsuzo; Sugano, Shigeki
ABSTRACT: We previously developed a four-arm, four-flipper disaster response robot called OCTOPUS to perform complex tasks at severe disaster sites. Its 22 degrees of freedom (DOF) enable advanced mobility and workability, but requires a minimum of two operators to control it. Considering the limitations of the current automated systems and the need to reduce human resources, it is practical to control OCTOPUS through a shared control. This entails a human-automation (HA) control system that independently allocates control authority between a human and automated system so as to simultaneously cover all DOF in what we call 'separative shared control'. To establish an HA control system, control authority allocation (CAA) must be carefully designed. We first performed experiments with a human-human (HH) control system using a VR simulator. We determined four tasks and five CAAs and then selected the optimum CAA by analyzing the results. We then developed an HA control system utilizing the selected CAA that replaces either human operator with a simple automated system. We compared the performance of the HH and HA control systems in the above four tasks using the VR simulator and found that the HA achieved less workload and higher subjective usability than the HH. GRAPHICAL ABSTRACT: